The Changing Collateral Space - Singh, Manmohan (IMF Working Papers; Working Paper ;, 2013)
This paper highlights the changing collateral landscape and how it may shape the global demand/supply for collateral. We first identify the key collateral pools (relative to the 'old' collateral space) and associated collateral velocities. Post-Lehman and continuing into the European crisis, some aspects of unconventional monetary policies pursued by central banks are significantly altering the collateral space. Moreover, regulatory demands stemming from Basel III, Dodd Frank, EMIR et cetera, new net debt issuance, and collateral connectivity via custodians (e.g., Euroclear/ Clearstream/ BoNY etc) will affect collateral movements.